Values, Interests and Power: South African foreign policy in uncertain times - Daniel D. Bradlow (Pretoria University Law Press (PULP), 2020)
About the publication South Africa's foreign policy makers are facing a substantial challenge. From the advent of the democratic era in 1994 through to the early 2000s, South Africa was a highly respected actor in international affairs with a number of impressive accomplishments in the areas of global governance, peacekeeping and international norm entrepreneurship. However, since that time, the country's international standing has declined. The value based and innovative foreign policy that earned the early post-apartheid South African government such great international respect has been replaced by a more transactional and tactically driven approach to international affairs. The country's position as Africa's leading economy and voice in international affairs is increasingly being challenged by other African states. This book explores how South Africa can develop a foreign policy strategy that is appropriate to the uncertain times in which we live and that both helps the country address its overwhelming domestic challenges of poverty, inequality and unemployment and regain its former high international reputation. The contributors to this book offer analyses and proposals for developing such a strategy within the context of the country's constitutional order and institutional constraints and that addresses the diverse and complex global and regional aspects of the country's international relations.